Structuralist Vs. Post-Keynesian Theory: Industrial Pricing in India - Dash, Santosh K (Asian Journal of Empirical Research, 2016)
How is industrial price determined in India? Using 40 years data spanning from 1970-71 through 2009-10 we provide fresh evidence to this question. We ask whether industrial pricing responds more to wage cost that rises with exogenous factors such as food prices (Structuralist theory) or to the endogenous need to finance new investment (i.e., Post-Keynesian theory). Though both the theories argue that industrial price is cost-determined, yet they differ in their methodology and thus, policy implication differs. We use Engel-Granger cointegration test and ARDL bounds test to answer the question. Since data support both the theories, a non-nested test is conducted where we find that the Structuralist theory outperforms its rival. This points out to the important role of agricultural goods in general, and food prices in particular in industrial price. The policy implication of this finding is that since agricultural prices play an important role in industrial price inflation, then monetary policy cannot control core inflation. Rather, the solution may lie in improving agricultural productivity through raising greater public investment.